MINAT KEPUTUSAN PEMBELIAN KONSUMEN TERHADAP SAYUR KEMAS SIAP MASAK (VEGETABEL MIX) DI UMKM PACK INSTAN - Aulia, Hermiza; Hartawaty, Dheny Arina (Agros Journal of Agriculture Science, 2024)
For busy consumers who prefer to consume vegetables without extra cutting or preparation, packaged vegetables are a convenient option. This study aims to identify the characteristics of respondents and test the influence of consumer interest on purchasing decisions in packaged vegetables UMKM. This study was conducted using interview and questionnaire techniques. The sampling technique used in this study was purposive sampling. Multiple regression analysis is the analysis method used in this study. The results of this study indicate that the variables of product quality, price, product diversity, and service quality have a significant effect on purchasing decisions simultaneously. The variable of product quality has a significant effect on purchasing decisions for packaged vegetables, while the variables of price, product diversity, and service quality do not have a significant effect on purchasing decisions for packaged vegetables partially.